Echocardiographic assessment of cardiovascular function and clinical outcomes in liver transplant recipients. Issue 11 (29th August 2022) - Lim, Wen Hui; Chew, Nicholas WS; Quek, Jingxuan; Ng, Cheng Han; Tan, Darren Jun Hao; Xiao, Jieling; Nah, Benjamin; Lee, Guan Huei; Huang, Daniel Q.; Tan, Eunice Xiang Xuan; Muthiah, Mark D.
Abstract: Background & Aims: Cardiovascular disease contributes to a high rate of morbidity and mortality after liver transplantation (LT). However, the progression of cardiac function and cardiac remodeling in LT recipients remains poorly understood. This study sought to evaluate the progression of cardiac function and structure in LT recipients and identify independent predictors of prognosis using echocardiography. Methods: From 2009 to 2019, 178 adult LT recipients at a tertiary academic transplant center were retrospectively studied. Transthoracic echocardiograms 1‐year pre‐ and post‐LT were assessed. Primary outcomes were progression of systolic and diastolic function. Secondary outcomes included left ventricular remodeling, all‐cause mortality, and heart failure readmission post‐LT. Subgroup analyzes were performed for etiology of native liver disease. A multivariable model was constructed to examine independent predictors of outcomes. Results: Systolic function significantly worsened, with reduction in stroke volume (45–37 ml/m 2, p  < .001), left ventricular ejection fraction (LVEF) (65%–62%, p  < .001) and cardiac index (3.00–2.60 L/min/m 2, p  < .001). Conversely, there were significant improvements in diastolic indices, including tricuspid regurgitation Vmax (228–215 cm/s, p  = .017), left atrial volume index (LAVI) (32–26 ml/m 2, p  < .001) and right ventricular systolic pressure (RVSP) (31–28 mmHg, p  = .001). Additionally, patients had increased relative wall thickness (RWT) ( p  < .001) and decreased left ventricular end‐diastolic dimension/body surface area ( p  < .001) post‐LT. The independent predictors for all‐cause mortality and heart failure were increased pre‐LT mitral annular early diastolic velocity (HR 1.11, CI 1.02–1.22, p  = .018), LAVI (HR 1.06, CI 1.02–1.11, p  = .007) and decreased LVEF (HR .89, CI .82–.97, p  = .006). The effect of non‐alcoholic steatohepatitis on cardiovascular outcomes post‐LT was largely comparable to that of Hepatitis B. Conclusion: This study showed reduced systolic and improved diastolic function in LT recipients and highlighted the utility of pre‐LT echocardiogram in the prognostication and risk stratification of LT candidates.